Spray-dried liposomes: A study of the effect of carbohydrate carrier and concentrations on liposome size and drug entrapment - Hussein, Nozad Rashid (Zanco Journal of Medical Sciences (ZJMS), 2019)
Background and objective: Dry powder inhalation provide many promising features for drug delivery to the pulmonary system, such as localization of drug within the lungs, drug retention in the respiratory tract, and reduced systemic toxicities. This study aimed to prepare dry powders of liposomes containing salbutamol sulfate using spray drying and study the influence of carrier type and concentration on liposome size and drug entrapment following rehydration of liposomal powder. Methods: Ethanol based proliposomes technique was used to generate liposomes containing salbutamol sulfate. Carbohydrate carriers: lactose, trehalose, sucrose, and mannitol in 1:6 or 1:10 (w/w) lipid to carrier ratio were separately incorporated into liposome formulations and dried by Büchi Mini-SprayDryerB-290. The protective effects of the sugars were investigated in terms of product yield (%), volume median diameter and size distribution of liposomes and entrapment efficiency of the drug. Results: The product yield (%) of spray dried liposome formulations with carriers was in the following order; trehalose (94.02 ± 1.20%) > sucrose (69.91 ± 1.75%) > lactose (68.30 ± 1.14%) > mannitol (50.16±0.80%) for the 1:6 formulations. Depending on the carrier type and lipidto carrier ratio, the vesicle size of liposomes with lactose and mannitol increased significantly (P <0.0001 and P = 0.0027, respectively), while the vesicle size with trehalose and sucrose varied to a lesser extent (P >0.05) compared to the control formulations (3.6µm ±0.24). For 1:10formulation, the vesicle size with mannitol (P <0.001) and sucrose (P <0.001) increased significantly. The drug entrapment efficiency using the 1:6 formulations was 20.74±1.78% for sucrose, 35.59±2.42% for trehalose, 67.21±1.89 % for lactose, and 80.84±3.64% for mannitol. Conclusion: Stable spray-dried liposomes were manufactured using sugars as carriers. The findings of this study have demonstrated the potential using of carbohydrate carriers to increase the physical stability of liposomes during the drying process, and trehalose can offer formulations with most desirable characteristics, while mannitol showed the least benefits.